2020
DOI: 10.1126/sciadv.aax5343
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic and terrestrial cyanobacteria produce methane

Abstract: Evidence is accumulating to challenge the paradigm that biogenic methanogenesis, considered a strictly anaerobic process, is exclusive to archaea. We demonstrate that cyanobacteria living in marine, freshwater, and terrestrial environments produce methane at substantial rates under light, dark, oxic, and anoxic conditions, linking methane production with light-driven primary productivity in a globally relevant and ancient group of photoautotrophs. Methane production, attributed to cyanobacteria using stable is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
189
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 228 publications
(242 citation statements)
references
References 74 publications
11
189
4
2
Order By: Relevance
“…While the hypolimnion is dominated by methanotrophy and hydrogenotrophic methanogenesis, the epilimnion is dominated by CH 4 originating from acetoclastic production, in situ or transferred from surrounding terrestrial ecosystems. The segregation between the CH 4 cycle in the epilimnion and the hypolimnion has been suggested by several reports 5,8,10,12,13 and used as a supporting evidence that epilimnetic CH 4 is locally produced 8,[10][11][12][13]27 or transported from the littoral zone 1,8,28 . In addition to similar conclusions, the present work was based on an innovative high resolution and sensitive method for determining C CH4 , which allowed the NMPR profile to be created and demonstrated that methanotrophy can occur well below the oxycline and euphotic zone of a lake.…”
Section: 18mentioning
confidence: 87%
“…While the hypolimnion is dominated by methanotrophy and hydrogenotrophic methanogenesis, the epilimnion is dominated by CH 4 originating from acetoclastic production, in situ or transferred from surrounding terrestrial ecosystems. The segregation between the CH 4 cycle in the epilimnion and the hypolimnion has been suggested by several reports 5,8,10,12,13 and used as a supporting evidence that epilimnetic CH 4 is locally produced 8,[10][11][12][13]27 or transported from the littoral zone 1,8,28 . In addition to similar conclusions, the present work was based on an innovative high resolution and sensitive method for determining C CH4 , which allowed the NMPR profile to be created and demonstrated that methanotrophy can occur well below the oxycline and euphotic zone of a lake.…”
Section: 18mentioning
confidence: 87%
“…For example, increasing near-surface turbulence and increasing winds can increase the magnitude of CH 4 diffusing across the air-water interface (Bastviken et al, 2004;Poindexter et al, 2016;Poindexter & Variano, 2013;Yang et al, 2013). In addition, elevated epilimnetic autochthonous production can increase CH 4 diffusion by providing labile organic matter to the sediments, which can stimulate pore water methanogenesis (Peeters et al, 2019), as well as providing labile material for oxic CH 4 production and generating anoxic microniches that produce CH 4 in the water column (Bižić et al, 2020;Bogard et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The large genome size compared to most phages known to date may include genes required for host range expansion. Given that Cyanobacteria produce O 2 that is required for methane oxidation by methanotrophs, and a very recent study indicated the production of methane by Cyanobacteria 45 , it is possible that future work will show that pmoC-phages with broad host range can have far reaching impacts on the methane cycle.…”
Section: Potential Biogeochemical Impacts Of Pmoc-phagesmentioning
confidence: 99%